Effect of Recombinant Human Epidermal Growth Factor Associated with Conventional Drug Therapy on the Dry Eye Symptom Score in Patients with Dry Eyes after Cataract Surgery: A Systematic Review and Meta-Analysis - Changce Sun; Xiaojun Zhang (Journal of Ophthalmology)
Objective. This study aimed to systematically assess the effect of recombinant human epidermal growth factor (rhEGF) associated with conventional drugs on the score of dry eye symptoms in patients with dry eyes after cataract surgery. Methods. The online database was searched for the clinical controlled trials of rhEGF associated with conventional drugs in the therapy of dry eyes after cataract surgery. Until now, the retrieval timeframe is based on the establishment of the database. Separately, two researchers extracted the data. The bias risk of each included literature was assessed. Results. Eight clinical controlled studies were finally included, with 878 samples. The success rate of the study group was greatly higher, and the difference was statistically significant (P<0.05). The fluorescein staining (FL) score of the research group after treatment was lower, and the difference was statistically significant (P<0.05). Compared with the control group, the tear break up time (BUT) of the study group after treatment was notably prolonged. The dry eye symptom score of the research group after treatment was notably lower, and the difference was statistically significant (P<0.05). Conclusion. Sodium hyaluronate associated with rhEGF eye drops is successful to treat xerophthalmia after cataract operation. It successfully promotes corneal healing, promotes tear film stability, and increases basic tear secretion. This treatment scheme is worth popularizing and applying in clinics.